Desarrollo de los procesos de mantenimiento eléctrico del sistema de potencia de 115 kV de la subestación belén de Cúcuta (2023)
In this document of the Electromechanical Maintenance Project, as a degree project to obtain the title of Technologist in Industrial Electromechanical Maintenance, the implementation and documentation of the predictive, preventive and corrective maintenance of the 115 KV bays that make up the electrical power system of the Belén substation owned by Centrales Eléctricas de Norte de Santander S.A. E. S. P, contains and contemplates the factors that influence when carrying out different types of maintenance, safety, voltage levels and type of bays in the electrical complex.